Estimating the rank of the spectral density matrix - Gonzalo Camba-Méndez; George Kapetanios (European Central Bank (ECB), 2004)
The rank of the spectral density matrix conveys relevant information in a variety of statistical modelling scenarios. This note shows how to estimate the rank of the spectral density matrix at any given frequency. The method presented is valid for any hermitian positive de?nite matrix estimate that has a normal asymptotic distribution with a covariance matrix whose rank is known.
Keywords: C12; C32; C52; 330; Spectral Density Matrix; Tests of Rank